Pendampingan Belajar Pola Bilangan untuk siswa Kelas VIII di SMP Negari 2 Kalabahi - Ronapli Blegur Wabang; Lois Letidena; Oktovian Meriance Lonawata; Jeni Marianti Loban; Melki Imamastri Puling Tang (Yayasan Literasi Sains Indonesia, 2023)
Community service activities carried out during the campus teaching assignment period 4, namely assisting in learning mathematics for class VIII students at SMP Negeri 2 Kalabahi, the purpose of this mentoring activity is to increase students' understanding, enthusiasm and enthusiasm for learning, especially in mathematics subject material about number patterns. Grade VIII students of SMP Negeri 2 Kalabahi have low interest in mathematics, this can be seen from their lack of enthusiasm in learning in class and their low understanding of the material provided. This is known through observation and initial assistance in class. Teaching and learning assistance activities for students using test methods, lectures, discussions and problem solving methods. At the beginning of this mentoring activity, students gave an initial test (pretest) with the aim of being able to find out the abilities of students before carrying out mentoring. After being given assistance by the service team, students will be given a final test (posttest) with the aim of knowing the level of success of the assistance carried out. The results of this activity have a very good and enthusiastic response from students to take part in good tutoring which can increase understanding, students in learning mindsets.